Synthesis of isoamyl esters from soybean oil deodorizer distillate by enzymatic catalysis for biolubricant applications - Silva, Rafael de Araujo (2022)
Lubricants are among the many products whose manufacture is highly dependent on nonrenewable fossil resources, with high levels of production and a vast marketplace, so they are the focus of many environmental laws around the word. Currently, this market includes some biobased products, known as biolubricants, although they represent a very small fraction of this sector and have certain limitations. Studies concerning the development of new products, raw materials, and processes are essential for the expansion and commercial success of biolubricants. Therefore, the aim of this work was: evaluating the production of biolubricant base stocks such as fatty acid isoamyl esters (FAIEs) from soybean oil deodorizer distillate (SODD) as a fatty acids source, together with isoamyl alcohol (a byproduct from bioethanol fermentation and the main constituent of fusel oil), catalyzed by free Eversa Transform 2.0 lipase and Pseudomonas fluorescens lipase (PFL) immobilized by the hybrid nanoflower (hNF) method. Experimental design and response surface methodology were applied to define the parameters for PFL immobilization using hNFs (hNF-PFL), viz. protein concentration, metal concentration and immobilization pH, and for FAIEs production, viz. SODD/isoamyl alcohol molar ratio, reaction temperature, the enzyme mass and secant salt mass (for the reactions with hNF-PFL). Studies of the incubation step of the synthesis using hNF-PFL enabled the incubation time to be reduced from 72 h (static immobilization medium at 25 °C) to just 20 min using ultrasound, without losses of immobilization yield (IY) or immobilized activity (IA). The optimized IY and IA values for hNF-PFL were 54 and 64 TBU%, respectively. The hNF-PFL showed high operational stability, maintaining practically the same reaction yield (RY) values during 8 cycles, over a total of 192 h. At the 10th cycle (total of 240 h), the material presented relative RY of 80%, compared to the earlier cycles. In the production of FAIEs using ETL 2.0 with molecular sieve (for moisture control) at 39 and 9 wt.% (molecular sieve mass / SODD mass), RY values of 50 and 70 wt.% were achieved, respectively. When hNF-PFL was employed in the FAIEs synthesis, RY of 64 wt.% was obtained, without the use of a moisture control agent. Products of partial conversion of SODD into FAIEs, catalyzed by ETL 2.0, with RY of 44 and 55 wt.%, and catalyzed by hNF-PFL, with RY of 56 and 57 wt.%, presented physicochemical characteristics similar to those of commercial biolubricant base stocks. Therefore, this doctoral thesis has the potential to contribute economically to the lubricant market through an environmentally friendly enzymatic process for the synthesis of a base stock from by-products of the national industry.